Strengthening Students’ Scientific Literacy: Development of the Creative Problem Solving Based E-Module of Buffer Solution - Arif Sholahuddin; Mia Febriani; Abdul Hamid (Jurnal Pendidikan Kimia Indonesia, 2025)
This research aims to develop a creative problem solving-based e-module on buffer solution material that is feasible for enhancing scientific literacy. The ADDIE development model was employed, encompassing the Analysis, Design, Development, Implementation, and Evaluation phases. During development, validity was tested by five experts/practitioners, readability was assessed through one-to-one testing with five students, and initial practicality and effectiveness were evaluated with a small group of 14 students. In the implementation phase, a field test involving 36 students assessed the final practicality and effectiveness. The study concluded that the developed e-module is feasible to use because it is (1) very valid, with an expert/practitioner validation score of 95.77, (2) very practical, with student response scores of 3.20 (good), teacher response scores of 3.5 (very good), teacher ability in using the e-module scored at 4.00 (very good), and the ability to manage the class using the e-module scored at 3.63 (very good), and (3) very effective, with a science literacy N-gain score of 0.83.